The Differences of Antibacterial Activity of Gambier Leaf Extract (Uncaria gambir Roxb.) with Various Solvents Against Enterococcus faecalis - Alfiyyah Putri Fajar; Trisnawaty K; Siti Rusdiana Puspa Dewi (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: Gambier leaves are herbal plants that have the potential to replace chlorhexidine to overcome root canal treatment failures where Enterococcus faecalis are commonly found. Various solvents such as n-hexane, ethyl acetate, ethanol, and distilled water extract from gambier leaves to increase antibacterial activity. Purpose: To determine the difference in antibacterial power of gambier leaf extract (Uncaria gambir Roxb.) with various solvents against Enterococcus faecalis. Methods: This study was an experimental in vitro laboratory investigation. The test group comprised extracts from gambier leaves using n-hexane, ethyl acetate, ethanol, and distilled water, all at a concentration of 10%, prepared through the graded maceration method. The antibacterial activity of these extracts was assessed using the disc diffusion method to determine the inhibition zone values. The results of the inhibition zones were analyzed statistically using one-way ANOVA and Post Hoc Tukey tests. Results: This study showed that a 10% ethyl acetate extract of gambier leaves had the highest average inhibition zone value of 16.10 mm, while a 10% distilled water extract of gambier leaves of 11.00 mm was the lowest. Statistically, there was a significant difference in the mean inhibition zone value between each group. Conclusion: The antibacterial power extract of gambier leaves (Uncaria gambir Roxb.) with a concentration of 10% with various solvents against Enterococcus faecalis showed a significant difference.